2017
DOI: 10.3389/fmicb.2017.01898
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Immunity Induced by H7N9 Avian Influenza Vaccines: Evaluation Criteria, Affecting Factors, and Implications for Rational Vaccine Design

Abstract: Severe H7N9 avian influenza virus (AIV) infections in humans have public health authorities around the world on high alert for the potential development of a human influenza pandemic. Currently, the newly-emerged highly pathogenic avian influenza A (H7N9) virus poses a dual challenge for public health and poultry industry. Numerous H7N9 vaccine candidates have been generated using various platforms. Immunization trials in animals and humans showed that H7N9 vaccines are apparently poorly immunogenic because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…H7N9 has caused huge economic and social losses due to its severity. Because of its pandemic potential, candidate vaccine seeds were produced in 2013 [16]. The H7N9 vaccines for poultry use have been formulated to prevent H7N9 viruses circulating in poultry at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H7N9 has caused huge economic and social losses due to its severity. Because of its pandemic potential, candidate vaccine seeds were produced in 2013 [16]. The H7N9 vaccines for poultry use have been formulated to prevent H7N9 viruses circulating in poultry at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse H7N9 vaccine candidates were generated and positive results were obtained from animal trials. However, only a few have been investigated in clinical trials in human volunteers [16]. Some H7N9 vaccines composed of viral-like particles, subunits, and split-virions have been evaluated in adults [28-33].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the threat of H7N9 influenza, different types of vaccine candidates have been generated, including whole-virus inactivated vaccines, subunit vaccines, virus-vectored vaccines and live attenuated vaccines (6,7). However, some studies have consistently shown that antibody immunity induced by H7N9 vaccines is qualitatively different from that observed for other influenza subtypes (H1N1, H3N2, and H5N1), which is characterized by low hemagglutination inhibition (HI) or virus neutralization antibody (nAb) but high levels of specific IgG antibody (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IIV are administered intramuscularly, leading to suboptimal induction of immune responses in the mucosa [ 45 , 176 ]. (ii) The intrinsic immunogenicity of the vaccine components, mainly the HA protein, can be responsible for the differences observed in the efficacy of seasonal IIV and/or LAIV [ 177 ]. (iii) The emergence of viral strain variants, distinct from the selected vaccine strain, during a given influenza season can result in significant loss of vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 99%